2008
DOI: 10.1110/ps.036384.108
|View full text |Cite
|
Sign up to set email alerts
|

Differential ubiquitin binding of the UBA domains from human c‐Cbl and Cbl‐b: NMR structural and biochemical insights

Abstract: The Cbl proteins, RING-type E3 ubiquitin ligases, are responsible for ubiquitinating the activated tyrosine kinases and targeting them for degradation. Both c-Cbl and Cbl-b have a UBA (ubiquitinassociated) domain at their C-terminal ends, and these two UBA domains share a high sequence similarity (75%). However, only the UBA from Cbl-b, but not from c-Cbl, can bind ubiquitin (Ub). To understand the mechanism by which the UBA domains specifically interact with Ub with different affinities, we determined the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Although few other UBA dimers have been identified or characterised, dimerisation of the UBA domains of the scaffold proteins c-Cbl and Cbl-b, [25][26][27] coupled with their capacity to control signalling downstream from many receptor-tyrosine kinases, suggests that dimerisation provides a mechanism for an expanded repertoire of Cbl-dependent signals. NMR titration studies estimated c-Cbl homodimerisation to be in the low micromolar affinity range; however, binding studies with an excess of Ub failed to produce any detectable interaction in HSQC experiments, suggesting that the functional role of the c-Cbl is not in regulating Ub interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few other UBA dimers have been identified or characterised, dimerisation of the UBA domains of the scaffold proteins c-Cbl and Cbl-b, [25][26][27] coupled with their capacity to control signalling downstream from many receptor-tyrosine kinases, suggests that dimerisation provides a mechanism for an expanded repertoire of Cbl-dependent signals. NMR titration studies estimated c-Cbl homodimerisation to be in the low micromolar affinity range; however, binding studies with an excess of Ub failed to produce any detectable interaction in HSQC experiments, suggesting that the functional role of the c-Cbl is not in regulating Ub interactions.…”
Section: Discussionmentioning
confidence: 99%
“…24 More recently, dimers have been characterised for the UBA domains of c-Cbl and Cbl-b involving hydrophobic surface interactions at the interface of helices 2 and 3. [25][26][27] The role of c-Cbl and Cbl-b as scaffold proteins, coupled with their capacity to interact with different downstream signalling proteins, suggests that dimerisation provides a mechanism for an expanded repertoire of Cbl-dependent signals recruited to receptor-tyrosine kinases. Although, in the case of the c-Cbl homodimer, Ub recognition does not appear to be its primary function, 25 the dimerisation and activation of the Ub protein ligase Cbl-b are Ub-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…Cbl is a RING-type E3 ubiquitin ligase that ubiquitylates receptor and non-receptor tyrosine kinases (8). Cbl contains a highly conserved N-terminal tyrosine kinase-binding (TKB) domain that mediates interaction between Cbl and phosphorylated tyrosines on activated receptor tyrosine kinases such as epidermal growth factor receptor (EGFR; ref.…”
Section: Introductionmentioning
confidence: 99%
“…A search using DALI (20), which interrogates the Protein Data Bank data base for structural homologues, showed that im23a had structural similarities to the ubiquitin-associated domain of the ubiquitin ligase Cbl-b (PDB ID 2DO6), which exists naturally as a dimer (21,22). An overlay of the two structures shows that the first two helices across the hairpin motif matched well with each other.…”
Section: Discussionmentioning
confidence: 99%
“…6C). The ubiquitinassociated domain consists of a compact three-helix bundle stabilized by a hydrophobic core (22); unlike im23a, the ubiquitin-associated domain does not contain any disulfide bonds to stabilize the structure. Several aspects of the NMR data for im23a (amide exchange rates, 3 J HNHA values, backbone chemical shifts, lack of medium-range NOEs) show quite clearly that its C-terminal region is not helical under the solution conditions examined here, and the Cys-26 to Cys-41 disulfide bridge dictates that the orientation of the C-terminal region is distinct from that in Cbl-b.…”
Section: Discussionmentioning
confidence: 99%